Effect of protonation on the solvation structure of solute N-butylamine in an aprotic ionic liquid. Issue 12 (8th February 2017) - Hashimoto, Kei; Fujii, Kenta; Ohara, Koji; Shibayama, Mitsuhiro
Abstract : Significant change in the solvation structure by protonation reaction in the ionic liquid [C2 mIm][TFSA]. Abstract : We report on the acid–base reaction of an amine solute in an aprotic ionic liquid from a structural point of view. Thus, the solvation structures of n -butylamine and n -butylammonium (BuNH2 and BuNH3 +, respectively, acid–base reaction: BuNH2 + H + ⇄ BuNH3 + ) in 1-methyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)amide ([C2 mIm][TFSA]) were investigated by high-energy X-ray total scattering combined with molecular dynamics simulations. We found that the solvation structure drastically changed as a result of the protonation reaction in [C2 mIm][TFSA]. The NH3 + group was preferentially solvated by TFSA − anions in the protonated BuNH3 + system, whereas the neutral NH2 group was surrounded by both TFSA − and C2 mIm + ions in the BuNH2 system. With regard to the nearest neighbor solute–TFSA interaction, the solvation number for TFSA − anions ( n TFSA ) increased upon protonation ( i.e. BuNH2 : n TFSA = 2 and BuNH3 + : n TFSA = 3). Both BuNH2 and BuNH3 + interacted with O atoms within TFSA − through hydrogen bonding ( i.e. N–H⋯O) interactions, and the N–H⋯O distance was appreciably shorter for positively charged BuNH3 + as compared to neutral BuNH2 . These results revealed that the solvation is more stable in energy for the protonated BuNH3 + group because of its stronger hydrogen bonding as compared to neutral BuNH2 . This is the origin of the large Gibbs energy for the protonation reaction (Δ G = −94.7 kJ mol −1 ) and the high acid dissociation constant (p K a = 16.6) of BuNH2 in [C2 mIm][TFSA] solution.